Exploring Internet Radio’s Impact on Dispersed Communities in Ghana - Braye, Alexander; Kroeze, Jan; Mujinga, Mathias (Universitas Bina Darma, 2025)
Due to the constant challenges that migrants face in their host country, which sometimes lead to alienation, they strive to find solace in internet radio connecting them to happenings in their home countries as well as the world. Satisfaction with information systems (IS) has long been a topic of research in the discipline. It has primarily been employed as a stand-in for IS success. Researchers have utilized DeLone and McLean’s 2003 extensive model of factors to evaluate IS performance and the interrelationships between the variables. According to their approach, the success of IS is largely dependent on user pleasure. They also suggested that the main antecedents of user happiness are system, information, and service success. Drawing clues from the major components of Delone and McClean’s IS success model, the article explores factors that influence the use of internet radio as an information system. The literature review reveals some attribute levels (accessibility, empathy, trustworthiness, etc.) that are confirmed and amended by the empirical study. The study uses a qualitative approach using interviews to collect data that examines the impact of internet radio on people living in dispersed communities. The results prompt key attributes of IS success, which are used to chart the impact of internet radio. The findings reveal that service success attributes (accessibility, empathy, etc.), data success (understandability and relevancy, etc.), and technology success attributes (availability, ease of use, etc.) impact the use of internet radio. Using the attributes identified in the literature review, as confirmed by the empirical study, as well as three additional constructs that emerged during the semi-structured interviews, a framework is developed to determine the impact of internet radio on dispersed communities. The research presents a novel comprehension of the impact of internet radio by applying and extending multi-attributes from the Delone and McClean IS success model.